Micelles in Cancer Therapy: An Update on Preclinical and Clinical Status - Aqeel, Rabia; Srivastava, Nidhi; Kushwaha, Poonam (Recent Patents on Nanotechnology, 2022)
Background: In the recent years, Micelles represent a promising carrier for the treatment and diagnosis of cancer. Architecturally, micelles are self-assembled nanosized colloidal aggregates prepared from amphiphilic surfactant with a hydrophobic core and hydrophilic shell. Such a composition makes them a potential carrier for delivery of hydrophobic anticancer drugs with in their core. Methods: Micelles have received increasing interest as an enhanced permeability and retention (EPR) targeted drug delivery systems for cancer treatment. Micelles can be modified to contribute various attractive properties, for instance, active targeting, stimuli-responsiveness. They have also proven their ability in drug targeting to tumor tissue, enhanced drug accumulation, drug stabilization, tissue penetration, prolong circulation, in vivo biocompatibility, biodegradability and reduced side effects. Micelles have displayed a vital role in multidrug delivery for cancer therapy. Results and Discussion: The aim of the present review is to provide an overview on the status of micellar nanoformulations for anticancer agents, including their pre-clinical and clinical researches. Emphasis is placed on presenting the newer strategies to enhance the therapeutic efficacy of anticancer drug at the target site. The type of co-polymers used and methods for the preparation of micelles are also highlighted in the paper.
Keywords: Critical Micelle Concentration (CMC)